1994
DOI: 10.1016/0014-5793(94)01177-x
|View full text |Cite
|
Sign up to set email alerts
|

The 26S proteasome of the yeast Saccharomyces cerevisiae

Abstract: Akatraet Proteasomes are large multicatalytic proteinase complexes found in all eukaryotic organisms investigated so far. They have been shown to play a central role in cytosolic and nuclear proteolysis. According to their sedimentation coefficients two types of these particles can be distinguished: 20s proteasomes and 26s proteasomes. In contrast to 20s proteasomes, which were mainly characterized on the basis of their ability to cleave small chromogenic peptide substrates and certain proteins in an ATP-indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 56 publications
2
26
0
1
Order By: Relevance
“…In this regard we note that while under our conditions almost all of the 19S/PA700 proteins can be found in association with the 20 S proteasome, an earlier report (46) found that unusual growth conditions were required to stabilize the 19S-20 S interaction. Given the dependence of the stability of 26 S to extract and growth conditions, and the possibility that other activators of the 20 S proteasome may compete with 19S/ PA700 for binding to the 20 S, we feel that the extent to which yeast 19S/PA700 is associated with the 20 S proteasome in vivo is still not clear.…”
Section: Discussionsupporting
confidence: 45%
“…In this regard we note that while under our conditions almost all of the 19S/PA700 proteins can be found in association with the 20 S proteasome, an earlier report (46) found that unusual growth conditions were required to stabilize the 19S-20 S interaction. Given the dependence of the stability of 26 S to extract and growth conditions, and the possibility that other activators of the 20 S proteasome may compete with 19S/ PA700 for binding to the 20 S, we feel that the extent to which yeast 19S/PA700 is associated with the 20 S proteasome in vivo is still not clear.…”
Section: Discussionsupporting
confidence: 45%
“…First, most of the proteasomes were removed from the crude extracts by ultracentrifugation at 100,000 ϫ g for 6 h (40). To confirm that the proteasome content was in fact reduced, we assayed the hydrolysis of Suc-Leu-Leu-Val-Tyr-MCA, a preferred substrate of the proteasome (41). This activity was 60 -70% lower after ultracentrifugation than in the whole extracts before centrifugation.…”
Section: Ubiquitin and Proteasomesmentioning
confidence: 99%
“…In addition, yeast genomic analysis using DNA chip technology reveals a 5 to 10 fold increase in mRNA transcripts of not only ubiquitin but also the Rpn1 (non-ATPase) and beta1 subunits of the 26S proteasome after exposure to a DNA-damaging agent (23). Furthermore, energy-dependent 26S proteasome assembly is enhanced in cell lysate prepared from nutrient depleted, heat-stressed yeast cells versus non-stressed cells (293). In some cancer cell lines, the proteasome is localized to the nucleus after stress (e.g.…”
Section: Eucaryal 26s Proteasomes and Stressmentioning
confidence: 99%